Electronic Waste Study & Facts in Bihar (International Journal of Engineering and Computer Science, 2014)
Increased market driven consumer behavior, increased purchasing power, competitiveness, fast changing socio economic pattern and demography of social set up and desire for ease in life style has changed the scenario of sophisticated toxic , deadly waste which requires special attaintion for handling and care for preservation of human kind generation. World convergence to global village resulting in transmigration of products and developed nation’s clever move to flow old obsolete discarded products in name of technology transfer to underdeveloped and developing nations is also responsible for e waste piling up. Disparity between have one and non having one is depleting but this is attracting world towards situation where one and all are being forced to sit on pool of deadly waste materials which will not see nations boundary but will pollute environment and atmosphere for all. In particular nation also situation of waste and waste handling is varied depending on populous demography and per capita income. States having less regard to norms and legislative frame work are worst effected compared to one which have sensible framework and are willing to address situation in attentive manner. Situation of Bihar state is in worst effected shape. Situation is similar to most of the underdeveloped nations scenario